2019
DOI: 10.1177/0956462419878043
|View full text |Cite
|
Sign up to set email alerts
|

Acceptability of a digital patient notification and linkage-to-care tool for French PrEPers (WeFLASH©): Key stakeholders' perspectives

Abstract: The objective of this study was to describe stakeholders’ perspectives on the acceptability of WeFLASH© (AADISS, Paris, France), a digital smartphone sexually transmitted infection (STI) patient notification (PN) tool to be launched among French HIV pre-exposure prophylaxis users (PrEPers). In Paris, Lyon, and Nice, we conducted 2-hour focus group discussions with PrEPers (n = 21) and community mediators (n = 10), and one-on-one interviews with PrEP-prescribing physicians (n = 5) and HIV/STI management decisio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…Security and privacy are common concerns with patient portals and are considered a major barrier to their uptake [40][41][42][43][44]. However, past research has found patients to be willing to accept confidentiality risks if they find some benefits like the convenience of online access to their personal health information [45] or to use an effective and useful mobile application [46]. Additionally, as suggested by this study's findings, measures can be applied to maximize security, including an automated logout after a certain time of inactivity and a two-step authentication process to log in and verify users' identity.…”
Section: Discussionmentioning
confidence: 99%
“…Security and privacy are common concerns with patient portals and are considered a major barrier to their uptake [40][41][42][43][44]. However, past research has found patients to be willing to accept confidentiality risks if they find some benefits like the convenience of online access to their personal health information [45] or to use an effective and useful mobile application [46]. Additionally, as suggested by this study's findings, measures can be applied to maximize security, including an automated logout after a certain time of inactivity and a two-step authentication process to log in and verify users' identity.…”
Section: Discussionmentioning
confidence: 99%
“…So it is more difficult to notify. 37 Another qualitative study noted similar benefits in their findings: Being anonymous might encourage the guy [partner] to reveal it [his HIV/ STI diagnosis]. 35 In contrast, hypothetical acceptability of appbased PN found that while 74% of 791 MSM participants were comfortable using anonymous PN, only 24% reported preference for using this method.…”
Section: Systematic Reviewmentioning
confidence: 94%
“…Nineteen of 26 studies were quantitative, [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] including one randomised controlled trial (RCT), 21 four were qualitative [34][35][36][37] and three were mixed methods studies. [38][39][40] Most explored established interventions (13/26), 16 21-26 28-30 32 38 39 nine explored hypothetical interventions, 15-19 35-37 40 five explored a mixture of implemented PN and hypothetical interventions, 20 27 31 33 34 detailed in tables 1-3 and online supplemental appendix C. The majority explored digital PN methods designed for use by the index patient (21/26).…”
Section: Overview Of Included Studies and Types Of Digital Interventi...mentioning
confidence: 99%
“…A summary of the article characteristics is in Table 2. Populations addressed included HIV pre-exposure prophylaxis (PrEP) users, 21 cisgender men and transwomen, 22 men who have sex with men (MSM), 17,23,24 people recently diagnosed with chlamydia 9,25 and the general population. 26 The eight articles used a range of qualitative and quantitative approaches.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…26 The eight articles used a range of qualitative and quantitative approaches. Five studies related to hypothetical digital PN interventions; 17,[21][22][23]26 only one reported solely on an intervention that had been delivered 25 and two concerned both real and hypothetical interventions. 9,24…”
Section: Study Characteristicsmentioning
confidence: 99%